Treating insomnia symptoms with medicinal cannabis: a randomized, crossover trial of the efficacy of a cannabinoid medicine compared with placebo. Issue 11 (11th June 2021) - Walsh, Jennifer H; Maddison, Kathleen J; Rankin, Tim; Murray, Kevin; McArdle, Nigel; Ree, Melissa J; Hillman, David R; Eastwood, Peter R
Abstract: Study Objectives: This randomized, double-blind, placebo-controlled, crossover study was conducted to evaluate the safety and efficacy of 2 weeks of nightly sublingual cannabinoid extract (ZTL-101) in treating chronic insomnia (symptoms ≥3 months). Methods: Co-primary study endpoints were safety of the medication based on adverse event reporting and global insomnia symptoms (Insomnia Severity Index [ISI]). Secondary endpoints included: self-reported (sleep diary), actigraphy-derived, and polysomnography measurements of sleep onset latency (SOL), wake after sleep onset (WASO), total sleep time (TST), sleep efficiency (SE); and self-reported assessments of sleep quality ( s SQ) and feeling rested upon waking. Adjusted mean differences between placebo and ZTL-101 were calculated. Results: Twenty-three of 24 randomized participants ( n = 20 female, mean age 53 ± 9 years) completed the protocol. No serious adverse events were reported. Forty mild, nonserious, adverse events were reported (36 during ZTL-101) with all but one resolving overnight or soon after waking. Compared to placebo, ZTL-101 decreased ISI (−5.07 units [95% CI: −7.28 to −2.86]; p = 0.0001) and self-reported SOL (−8.45 min [95% CI: −16.33 to −0.57]; p = 0.04) and increased self-reported TST (64.6 min [95% CI: 41.70 to 87.46]; p < 0.0001), s SQ (0.74 units [95% CI: 0.51 to 0.97]; p < 0.0001), and feeling of being rested on waking (0.51 units [95% CI: 0.24 to 0.78]; p = 0.0007). ZTL-101 also decreased actigraphy-derived WASO (−10.2 min [95% CI: −16.2 to −4.2]; p = 0.002), and increased actigraphy-derived TST (33.4 min [95% CI: 23.07 to 43.76]; p < 0.001) and SE (2.9% [95% CI: 2.0 to 3.8]; p = 0.005). Conclusions: Two weeks of nightly sublingual administration of a cannabinoid extract (ZTL-101) is well tolerated and improves insomnia symptoms and sleep quality in individuals with chronic insomnia symptoms. Clinical Trial: ANZCTR; anzctr.org.au ; ACTRN12618000078257.